RELATIONSHIP BETWEEN PREDISPOSITION FACTORS AND PREGNANT INITIATION PLANNING FOR PREGNANT WOMEN IN LEGOK SUB-DISTRICT JAMBI CITY IN 2018 - Diniyati Diniyati; Titik Hindriati; Kiki Andriana (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2018)
Abstract : Nutritional Status Monitoring results in 2016, the percentage of newborns who received IMD in 2016 was 51.9% which consisted of 42.7% getting in <1 hour after birth, and 9.2% ≥ one hour or more. The highest percentage was in DKI Jakarta Province (73%) and the lowest was Bengkulu (16%). The percentage of infants 0-5 months who still received exclusive breastfeeding was 54.0%, while infants who had exclusive breastfeeding until the age of six months amounted to 29.5% (Ministry of Health, 2016: 138). This study is an analytical study with cross sectional approach, which aims to determine the relationship of predisposing factors with planning of Early Breastfeeding Initiation of pregnant women in Legok Village, Jambi City in 2018. This study was conducted in Legok Village, Jambi City. The population of this study were 241 pregnant women and a total sample of 69 people. The sampling technique uses accidental sampling technique. This research will be carried out in July 2018. The data analysis used is univariate and bivariate analysis. The results showed that there was a significant relationship between knowledge with planning for early breastfeeding initiation of pregnant women in Legok Village, Jambi City with a p value of 0.002 and a meaningful relationship between perceptions of Early Breastfeeding Initiation planning for pregnant women in Legok Village, Jambi City with a p value of 0.005. It is expected that health workers will conduct joint discussions with pregnant women about the importance of Early Breastfeeding Initiation (IMD) planning, so that mothers have more in-depth information, especially about the definition of Early Breastfeeding Initiation and the management of Early Breastfeeding Initiation Keyword : Early Breastfeeding Initiation, pregnancy